STUDY ON THE TECHNIQUE OF THE GAME OF BADMINTON BY USING INFORMATION TECHNOLOGY DURING THE PANDEMIC COVID -19 IN STUDENTS AGED 10-12 YEARS - Tănasă Bogdan Ionuț; Vizitiu Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
In middle school education, sports games have always been attractive activities for students. Among the many sports games, we will propose a study to learn the technique of badminton during the COVID 19 pandemic, using online information technology. In this sense, we will focus on learning the basic technical elements, namely: the fundamental position, the movement in a space in a room and the grip of the rocket, without causing injuries. The research took place at the "Alexandru Ioan Cuza" Secondary School in Fălticeni, including students (girls and boys) from the 5th and 6th grades. The aim of the study is to correctly master the three fundamental elements of the game of badminton, having a decisive role on the evolution of student players. Through the online program "Google Meet", we imposed a clarification on students, namely: to face the monitor to see how the technique is performed and the number of repetitions. This new way of conducting the teaching-learning process in badminton lessons has many good parts, but we must mention that it also has some less good parts.